The Upside of Negative Emotions: How Do Older Adults From Different Cultures Challenge Their Self-Growth During the COVID-19 Pandemic? - von Humboldt, Sofia; Mendoza-Ruvalcaba, Neyda Ma.; Arias-Merino, Elva Dolores; Ribeiro-Gonçalves, José Alberto; Cabras, Emilia; Low, Gail; Leal, Isabel (Frontiers in Psychology, 2022)
Background and objective: The outbreak of Coronavirus Disease 2019 (COVID-19) has raised increased challenges for older adults’ personal growth in diverse cultural settings. The aim of this study was to analyze negative emotions and their role on older adults’ self-growth from Mexico, Italy, Portugal, and Spain, during the COVID-19 pandemic. For this purpose, a cross-national qualitative research was carried out. Methods: Data were collected from 338 community-dwelling participants aged 65 years and older, using a semi-structured interview protocol. Older adults were asked about negative emotions that significantly contribute to their self-growth during the COVID-19 pandemic. Content analysis was used to identify key themes. Results: Seven main negative emotions (fear, sadness, anger, grief, boredom, loneliness and shame) significantly contributed to seven themes of self-growth, across the samples: sharing difficult experiences with others, supportive partner, spiritual practices, engagement with life, generativity, volunteering activities, and intimacy and sexual satisfaction. Sharing difficult experiences with others was most pertinent to Mexican (13.9%) and to Italian (3.0%) participants, and a supportive partner to Portuguese (12.1%), and to Spanish participants (6.5%). The strongest correlations were between sadness and supportive partner (r=.76; p=.01) and between sadness and difficult experiences with others (r=.74; p=.01). Conclusions: The findings of this study indicate that negative emotions during the COVID-19 pandemic contributed to their older adults’ self-growth. This study highlighted the cultural diversity of experiences during the pandemics, and underlined the upside of negative emotions and its relation to older adults’ self-growth during this period.